Analisis Implementasi Transaksi Kliring Menggunakan Aplikasi Reservasi Digital Terhadap Efisiensi Operasional Di Perbankan - Kurniawan, Sunny Agung; Cholifihani, Muhamad; Rustanto, Agung Edi; Waluyo, Surryanto Djoko (Gorontalo Accounting Journal, 2025)
This research evaluates the effectiveness of the clearing system and digital reservation applications in public administration within the banking sector. These applications enhance service efficiency, allowing customers to schedule their visits and reducing waiting times. A qualitative research method with triangulation was employed, including interviews, observations, and documentation. The findings indicate that the application can improve operational efficiency, although usability and data security challenges exist. Some customers faced difficulties, highlighting the need for interface improvements and additional training. The conclusion emphasizes the importance of enhancing information access and IT security systems for broader digital adoption.